2006
DOI: 10.1113/jphysiol.2006.115691
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic origin of CB1‐dependent tonic inhibition of GABA release at cholecystokinin‐positive basket cell to pyramidal cell synapses in the CA1 region of the rat hippocampus

Abstract: Cholecystokinin-positive (CCK+) basket cells are a major source of perisomatic GABAergic inputs to CA1 pyramidal cells. These interneurons express high levels of presynaptic cannabinoid type 1 (CB1) receptors that mediate short-term depression of GABA release following depolarization of postsynaptic cells. However, it is not known whether GABA release from CA1 CCK+ basket cells is under tonic endocannabinoid inhibition. In paired patch-clamp recordings, action potentials in presynaptic CCK+ basket cells evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
185
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(201 citation statements)
references
References 48 publications
15
185
0
1
Order By: Relevance
“…3) are thought to play complementary roles to FSBCs, because of their different input and output properties (Hefft and Jonas, 2005;Földy et al, 2006;Glickfeld and Scanziani, 2006), regulation by modulatory systems Freund and Katona, 2007;Neu et al, 2007) and in vivo firing properties (Klausberger et al, 2005). In our sample, all RSBCs had the majority of their axons arborizing in the pyramidal cell layer of CA3 (24 of 24; all cells), forming large, closely placed boutons.…”
Section: Specific Description Of Cell Typesmentioning
confidence: 96%
“…3) are thought to play complementary roles to FSBCs, because of their different input and output properties (Hefft and Jonas, 2005;Földy et al, 2006;Glickfeld and Scanziani, 2006), regulation by modulatory systems Freund and Katona, 2007;Neu et al, 2007) and in vivo firing properties (Klausberger et al, 2005). In our sample, all RSBCs had the majority of their axons arborizing in the pyramidal cell layer of CA3 (24 of 24; all cells), forming large, closely placed boutons.…”
Section: Specific Description Of Cell Typesmentioning
confidence: 96%
“…Tracing studies had established that CCK hippocampal interneurons receive cholinergic inputs from the septum (Woolf, 1991) and serotonergic afferents from the median raphe nucleus (Freund et al, 1990). In addition, electrophysiological analysis determined that the tonic control of GABA release from hippocampal CCK cells is regulated through the modulation of the synthesis and release of endocannabinoids from the postsynaptic pyramidal neurons (Kim et al, 2002;Neu et al, 2007). The complex composition of these α7 nACh/ 5HT3 A /CB1/CCK interneurons is in line with the suggestion that hippocampal CCK neurons relay inputs from diverse cortical and subcortical regions about emotional, motivational, and physiological states (Freund, 2003).…”
Section: Hippocampal α7 Nach/cb1/5ht3 a /Cck Interneuronsmentioning
confidence: 99%
“…In addition, we determined that, with exception of the s. oriens, in both the hippocampus and the DG the interneurons co-expressing α7 nACh mRNA and CB1 mRNA constitute the major population of CB1 containing interneurons. Based on the high degree of co-localization of α7 nACh mRNA and CB1 in these interneurons, it is likely that their GABAergic neurotransmission will be regulated by the synthesis and release of endocannabinoids from the postsynaptic pyramidal neurons (Kim et al, 2002;Neu et al, 2007) and by their cholinergic innervations from the medial septum and diagonal band (Woolf, 1991).Interneurons expressing α7 nACh mRNA constitute a subpopulation of CCK containing neurons in the hippocampus and the DGWe found that, with the exception of the s. oriens, in both the hippocampus and the DG 40-79% of all interneurons expressing α7 nACh mRNA contain CCK. In contrast, within the s. oriens only 20% of all interneurons expressing α7 nACh mRNA have CCK.…”
mentioning
confidence: 99%
“…In the methods described above, pharmacological isolation and paired recordings are used to assess post and presynaptic GABA B R-mediated effects, respectively; however one can easily modify the combination of receptor agonists and antagonists to assess the role of alternative receptor families, for example the cannabinoid system 21 …”
Section: Discussionmentioning
confidence: 99%